Relevance of the Remedial Secession Theory for Indonesia's Territorial Integrity - Triyana, Heribertus Jaka (UI Scholars Hub, 2023)
This article aims to analyse the remedial secession theory in international law relevant to the current international armed conflict between Russia and Ukraine waged by Russia’s recognition of Donbask and Luhansk independence. It might have legal as well as political impacts on the territorial integrity of a sovereign State such as Indonesia where human rights violations in Papua have become problematic. The analysis in this paper is mainly construed using the paradigm of customary international law as the primary source of international law to find out the relevance of the remedial secession theory in terms of its area, scope, and institutionalization. It provides a framework of analysis on how the state provides elements of legitimate expectation and authority: justification and legitimacy over unclear and/or public discourse on the application of remedial secession theory. This article reveals that remedial secession theory has been practiced under the legal notion of the right of self-determination beyond the decolonization context with certain cumulative requirements, such as the factual existence of gross violations of human rights, last resort, and recognition from the mother country and/or other countries. Secondly, it has relevance for the territorial integrity of a sovereign country since it supports changing the paradigm of international from state sovereignty to sovereignty as responsibility. In this regard, the sovereign state is under an international obligation to respect and protect its own nationals since gross human rights violations committed by the state have been accepted as threats to international peace and security.